Auditory Stimulation Dishabituates Olfactory Responses via Noradrenergic Cortical Modulation - Jonathan J. Smith; Kiseko Shionoya; Regina M. Sullivan; Donald A. Wilson (Neural Plasticity)
Dishabituation is a return of a habituated response if context or contingency changes. In the mammalian olfactory system, metabotropic glutamate receptor mediated synaptic depression of cortical afferents underlies short-term habituation to odors. It was hypothesized that a known antagonistic interaction between these receptors and norepinephrine ß-receptors provides a mechanism for dishabituation. The results demonstrate that a 108 dB siren induces a two-fold increase in norepinephrine content in the piriform cortex. The same auditory stimulus induces dishabituation of odor-evoked heart rate orienting bradycardia responses in awake rats. Finally, blockade of piriform cortical norepinephrine ß-receptors with bilateral intracortical infusions of propranolol (100 μM) disrupts auditory-induced dishabituation of odor-evoked bradycardia responses. These results provide a cortical mechanism for a return of habituated sensory responses following a cross-modal alerting stimulus.